Optimising the Role of Trainers Through the Use of Educational Technology for the Professional Development of Government Officials - Ika Wulansari; Yudan Hermawan; Kiki Irafa Candra (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
This study analyses the optimisation of trainers’ roles in enhancing the professionalism of village government officials through the use of educational technology. Employing a qualitative descriptive case study design, the research was conducted at the Yogyakarta Village Government Training Centre, involving 23 participants—eight trainers and fifteen village officials. Data were collected through in-depth interviews, participatory observation, and document analysis, and analysed using a thematic model (Saldana, 2014). The findings reveal six interrelated strategic functions of trainers: learning facilitators, contextual material designers, motivators, post-training mentors, policy translators, and change agents. The integration of educational technologies—such as online platforms, digital simulations, and virtual mentoring—enhanced learning effectiveness and fostered a sustainable professional development ecosystem. The study concludes that professionalism among officials is shaped not only by the content of training but also by the quality of digital facilitation and continuous socio-technical support.